Childhood poisoning in Sagamu, Southwest, Nigeria - Oba-Daini OO; Ogunlesi TA; Adekanmbi AF; Akodu SO (Nigerian Journal of Paediatrics, 2024)
Background: Childhood poisoning is an important cause of childhood morbidity and mortality, especially in children below five years of age. There is an increase in the range of household poisoning agents, particularly cheap hydrocarbon domestic fuel such as kerosene (paraffin).